IMPLEMENTASI NILAI-NILAI BUDAYA, SOSIAL, DAN LINGKUNGAN PENGEMBANGAN DESA WISATA DI PROVINSI YOGYAKARTA - Joko Tri Haryanto (Jurnal Kawistara, 2013)
Although giving a huge benefit to the developing of social welfare in the world, tourism development has also often ces of the environmental damage, when especially requiring for infrastructure development. However, along with increased awareness of the importance of environmental functions, isustainable tourism or usually called ecotourism has developed with many different kinds. Yogyakarta, as one of tourist destinations in Indonesia, has developed cultural values, social, and environment based ecotourism in the form of Tourism Village. This kind of Tourism Village has not unfortunately, identified and used social, cultural, and environmental values as among the main attractions. for this reason this paper is written to provide guidance for implementing the cultural values, social, and environment based eco-tourism in order to develop the Tourism Village.